Numerical study on the heat transfer characteristics of a liquid lead–bismuth eutectic in a D-type channel - Liu, Hong; Zhang, Zhigang; Du, Haisu; Cong, Tenglong (Frontiers in Energy Research, 2022)
A printed circuit heat exchanger (PCHE) can offer superior performance in area concentration and heat transfer efficiency. A PCHE with a liquid lead–bismuth eutectic (LBE) and supercritical carbon dioxide as working media can use these materials as intermediate heat exchangers in lead–bismuth eutectic-cooled reactors to reduce facility size and improve economy. To ensure the reliability of a numerical simulation for a liquid LBE in PCHE channels, the flow and heat transfer characteristics of a liquid LBE were investigated in a single D-type channel. The existing turbulent Prandtl number ( ) models and the shear‒stress transport (SST) model were evaluated first by using experimental liquid metal data. Then, a suitable model was proposed for the numerical simulation of the liquid LBE. Finally, the flow and heat transfer characteristics of the liquid LBE were studied in D-type straight channels and D-type zigzag channels. The study presented the effects of flow velocity, wall heat flux, equivalent diameter and zigzag channel angle on the flow resistance and heat transfer characteristics. Meanwhile, a heat transfer correlation suitable for a D-type straight channel was also proposed. The research results in this paper lay a good foundation for the development of PCHEs with an LBE as the working fluid.